(untitled) (Bangladesh Journal of Public Administration, 2025)
Culture shapes behavior and society and eventually it shapes a society’s common phenomena. Extrajudicial killings are widespread in Bangladesh. Extrajudicial killing threatens rule of law and human rights. This study assessed how culture affects extrajudicial killings by law enforcement agencies in Bangladesh. This study employed qualitative design and data was collected through in-depth interviews with purposively sampled respondents and content analysis of secondary sources. Based on the famous cross-cultural theory of Greet Hofstede, depending on five distinct cultural dimensions, data has been analyzed manually. Each of the dimensions of culture has been proven as influencing to the phenomena of extrajudicial killings except one. Four have been found to be associated with the phenomenon of extrajudicial killings in a way that their presence or absence may influence extrajudicial killings. However, ‘uncertainty avoidance’ could not be proven to influence extrajudicial killings though gathered data and secondary literature. Further research may reveal this specific dimension. However, this study has been concluded that cultural elements and practices have influence on the phenomenon of extrajudicial killing and based on the cultural values and norms of the society, pattern, incidents and perceptions of extrajudicial killing may vary.